Psychometric properties of the Reynolds Child Depression Scale in community and clinical samples - Figueras Masip, Anna; Amador Campos, Juan Antonio; Guàrdia Olmos, Joan Guàrdia (The Spanish Journal of Psychology, 2008)
The factor structure of the Reynolds Child Depression Scale (RCDS; Reynolds, 1989), analyzed by confirmatory factor analysis and the scale’s psychometric characteristics in a sample of 315 participants (140 boys and 175 girls) and a clinical sample of 62 participants (37 boys and 25 girls) between 10 and 12 years old, are presented. Two models are tested with confirmatory factor analysis: a one-factor model and a five-factor model. Both models show a good fit, but the one-factor model was chosen because it is the most parsimonious. The reliability coefficient ranged from .87 (at test) to .89 (at retest) in the community sample, and was .90 in the clinical sample (at test). Test-retest reliability was .66 in the community sample. Concurrent validity with other self-reports that measure depressive symptomatology was high, both in the community sample (.76) and the clinical sample (.71). There were no significant sex differences but there were differences due to age (school grade).